Development of multimedia-based learning videos to increase learning motivation in history for grade XI social science students in senior high school - Kristoforus Bagas Romualdi; Ajat Sudrajat (JINoP (Jurnal Inovasi Pembelajaran), 2024)
Students' motivation during history learning processes in the classroom is influenced, among other factors, by teachers' innovation in teaching. However, there are still teachers who lack innovation, resulting in decreased motivation for students to learn history. This study aims to develop and assess the feasibility of a product in the form of multimedia-based learning videos on the topic of Islamic Maritime Kingdoms, as well as to analyze its effectiveness in increasing the learning motivation of Grade XI Social Science students. The type of research used was research and development with ADDIE design. This study involved 2 experts, 2 teachers, and 75 students divided into 15 students for small-scale trials and 60 students for large-scale trials and extensive testing. Data collection was done through questionnaires using survey techniques and interviews. Data analysis techniques included quantitative and qualitative descriptive analysis, as well as descriptive statistics. The research results indicated that the product developed by the researcher was feasible for use as a learning media. Additionally, multimedia-based learning videos were also effective in increasing students' motivation to learn history.